2012
DOI: 10.1080/19415257.2012.657870
|View full text |Cite
|
Sign up to set email alerts
|

Professional development and job-embedded collaboration: how teachers learn to exercise leadership

Abstract: Research shows that professional development alone does not provide adequate leadership preparation for teachers, yet many develop into established teacher leaders. The purpose of this study was to explore how teachers learn to exercise informal leadership in the schools and districts where they work. Eight elementary teachers who lived and worked in the Midwestern region of the United States participated in the study. Data collection included written self-reflections, questionnaire responses and a participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 21 publications
6
71
0
8
Order By: Relevance
“…Accordingly, it can be said that teacher leadership behaviors in high schools increase in parallel with task-oriented, success-oriented, bureaucratic, and support-oriented culture. Factors that affect the development of teacher leadership include school principals supporting the staff in different aspects (Hart, 1994;York-Barr & Duke, 2004;Wenner & Campbell, 2016), giving teachers time to develop themselves (Chew & Andrews, 2010), the existence of learning communities in schools that ensure professional collaboration (Hunzicker, 2012;Chamberland, 2009), and an environment of trust and peace at school (Beachum & Dentith, 2004;Gordin, 2010;York-Barr & Duke, 2004). However, teachers' lack of time, poor communication, structural factors and personal characteristics (Wenner & Campbell, 2016), lack of shared vision (Brooks, Scribner, & Eferakorho, 2004), excessive workload, insufficient support (Adams & Gamage, 2008), and an authority and autonomy gap (Friedman, 2011) weaken teacher leadership.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it can be said that teacher leadership behaviors in high schools increase in parallel with task-oriented, success-oriented, bureaucratic, and support-oriented culture. Factors that affect the development of teacher leadership include school principals supporting the staff in different aspects (Hart, 1994;York-Barr & Duke, 2004;Wenner & Campbell, 2016), giving teachers time to develop themselves (Chew & Andrews, 2010), the existence of learning communities in schools that ensure professional collaboration (Hunzicker, 2012;Chamberland, 2009), and an environment of trust and peace at school (Beachum & Dentith, 2004;Gordin, 2010;York-Barr & Duke, 2004). However, teachers' lack of time, poor communication, structural factors and personal characteristics (Wenner & Campbell, 2016), lack of shared vision (Brooks, Scribner, & Eferakorho, 2004), excessive workload, insufficient support (Adams & Gamage, 2008), and an authority and autonomy gap (Friedman, 2011) weaken teacher leadership.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
“…In environments where teacher leadership is encouraged, practices towards ensuring collaboration among colleagues, school administrators' support, and a supportive work setting are significant (Demir, 2014). On the other hand, the elements that improve teacher leadership include principal support (Hart, 1994;York-Barr & Duke, 2004;Wenner & Campbell, 2016), teacher autonomy (Wenner & Campbell, 2016), providing teachers with time and resources (Chew & Andrews, 2010;York-Barr & Duke, 2004), common vision (Chamberland, 2009;Gaffney & Faragher, 2010;Muijs & Harris, 2006), sharing leadership (Brosky, 2011;Chamberland, 2009), school structure and processes (Beachum & Dentith, 2004), team leadership (Gaffney & Faragher, 2010), school-society relationships (Beachum & Dentith, 2004), learning communities (Chamberland, 2009;Gaffney & Faragher, 2010;Hunzicker, 2012), participation in decision-making and developing a common curriculum (Chew & Andrews, 2010), paying attention to trust, respect, and ethics at school (Beachum & Dentith, 2004;Gordin, 2010;York-Barr & Duke, 2004), well-defined tasks (Muijs & Harris, 2006), and a culture of constant development at school (Borchers, 2009). …”
Section: The Relationship Between School Culture and Teacher Leadershipmentioning
confidence: 99%
“…Reflecting on Hunzicker's (2012) research, carrying out leadership roles leads to growth and development professionally. Together, such conceptualizations suggest that teacher leadership development consists of three ideas, namely 'teacher participation, teacher learning and teacher influence' (Hunzicker, 2012: 276 Aubrey (2011: 13) suggested that there is a lack of leadership skills development within the context of Early Years, and this could be one reason why Early Years leaders may not consider themselves as leaders of learning and people.…”
Section: Leadership Skillsmentioning
confidence: 99%
“…Firstly, the dimension of occupational cooperation refers to the studies of teachers for common goals and cooperation. In schools in which occupational cooperation is supported, common goals and vision are created (Chamberland, 2009;Gaffney & Faragher, 2010;Muijs & Harris, 2006), and professional learning communities are developed (Chamberland, 2009;Danielson, 2006;Gaffney & Faragher, 2010;Harris & Muijs, 2005;Hunzicker, 2012;McCay, Flora, Hamilton, & Riley, 2001). Secondly, the school administrator supports teachers.…”
Section: School Culture That Supports Teacher Leadershipmentioning
confidence: 99%